Serotonin-depleted rats are capable of learning in active place avoidance, a spatial task requiring cognitive coordination - Petrásek, T; Stuchlík, A (Physiological research, 2009)
Neurotransmitter substrate of spatial cognition belongs to current topics in behavioral neuroscience. The present study examined the effects of serotonin depletion with p-chlorophenylalanine on learning of rats in active place avoidance, a spatial task requiring allothetic mapping and cognitive coordination and highly dependent upon hippocampus. Serotonin depletion transiently increased locomotor activity in response to footshocks, but it did not change the avoidance efficiency measured by three spatial parameters. These results suggest that serotonin neurotransmission is not crucial for cognitive coordination and allothetic learning, i.e. the processes, which are crucial for active place avoidance performance.
Keywords: kognice; fenklonin; potkani Long-Evans; Cognition; Fenclonine; antagonisté serotoninu; krysa rodu Rattus; Serotonin Antagonists; pohybová aktivita; vnímání prostoru; Rats, Long-Evans; Motor Activity; mužské pohlaví; Space Perception; zvířata; Rats; Animals; Male; Serotonin; serotonin; Avoidance Learning; učení vyhýbat se